Systematic Literature Review (SLR): Religious Tourism Development Strategy to Improve the Community Economy after Covid-19 - Ahmad Ravid Faradika Purnama (Indonesian Journal of Business Analytics, 2024)
The Covid pandemic has spread and spread globally, this has had an impact on the community's economy, especially in the tourism sector, many business actors have gone out of business due to the Covid pandemic, therefore this research aims to find strategies for developing religious tourism to improve the community's economy after Covid-19. This research method is qualitative research using the Systematic Literature Review (SLR) method. The SLR method was chosen by researchers because it is able to provide a concrete picture of the differences or relationships between one literature and another, so that it can provide conclusions or descriptions of certain thematic frameworks holistically, and can provide new directions or ideas to be followed up empirically. The results of this research show that each religious tourism destination has a different development strategy according to the problems faced in each religious tourism destination. d in each religious tourism destination.